NORMATIVE AND LEGAL REGIME OF LEGAL SERVICES QUALITY - V. A. Belov (Дискурс, 2017)
The problem of quality of legal services is considered, particular provisions of legal regulation of rendering legal services are analyzed. The standard legal regime covers category of quality both economic and legal. Legal services are various and presented by a multidimensional range. The quality problems of rendering various services are important for a consumer. The sphere of rendering legal services is rather extensive and anyway legal services have to be exposed to legal regulation. The functioning of a standard legal regime of quality of legal services is analyzed in the article not only their standard fixing, but also questions connected with the settlement of specific cases in practice.